PENDIDIKAN GRATIS DI ERA KAPITALIS DALAM USAHA PEMERATAAN HAK ATAS PENDIDIKAN - Permatasari, Anggi Novella; Syafi’i, Imam (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Education is the right of everyone to get the opportunity to develop their potential through a process called learning which is said to be able to break the chain of poverty. However, has the implementation of this statement been running properly in Indonesia? That every citizen has the same rights in the form of the opportunity to attend school to university? Is "Education for All" just an empty program? The basic concept of equal opportunity to receive education which is focused on equality in education and equity in education seems to have not worked out ideally or even hindered each other. Discrimination of society on the basis of status and class to obtain privileges in obtaining educational opportunities is also still the biggest enemy for the basis of education for all. All kinds of arguments were expressed, ranging from government regulations that change frequently, low public awareness of the importance of education, the education ladder that feels the need to sacrifice a lot of money, and free education policies that sometimes do not match the reality and expectations of the community. By going through the library research method, this journal will more or less discuss how the principle of free education is often found contradicting the practice of educational capitalism which is so rampantly multiplying in the middle of the 4.0 era which actually requires the younger generation from the lower classes to the upper classes to continue to develop and continue to explore their potential through education.